Comparison of gefitinib-induced skin adverse reactions (SAR) in C57BL/6 and FVB/N mice. Issue 2 (11th March 2021) - Zhang, Yali; Wang, Yalei; Chen, Ziwei; Cheng, Shuo; Ding, Chengcheng; Zhang, Jiani; Peng, Tiantian; Chen, Weihang; Zhang, Dingyang; Tan, Yan; Wang, Xu; Dong, Ruijuan; et al.
Abstract: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) such as gefitinib, erlotinib, and afatinib, are widely used in clinical practice and remarkably effective in treatment of advanced non-small cell lung cancer. However, there are some adverse effects while taking EGFR-TKIs, among which skin adverse reactions (SAR) are the most common events. At present, the poor outcome of SAR and insufficient research on SAR models need to be addressed. In this study we focused on the SAR models to lay a foundation for mechanism researches. Gefitinib, one of the EGFR-TKIs, was used as SAR inducing agents. We chose C57BL/6 and FVB/N mice as experimental model and they were divided into four groups. The weight and skin moisture of mice were detected every 7 days, itching behavior and abnormal eyelids were tested at 35th day after gavage, and survival rate was also recorded. The weight of unit area hair, length of whiskers and inflammatory cells were evaluated after mice sacrificed. C57BL/6 animals treated with gefitinib showed significant differences in survival rate, weight of unit area hair, skin moisture changes, skin dryness, itching behavior, whisker irregular growth, abnormal eyelids, and inflammatory cells; FVB/N animals treated with gefitinib only showed significant differences in survival rate, whisker irregular growth and abnormal eyelids, compared with the control group, respectively. In this study, we compared the similarities and differences of gefitinib-induced SAR between C57BL/6 and FVB/N mice, which illustrated different patients probably showing different symptoms clinically and provided experimental basis for researching mechanism of EGFR-TKIs induced SAR.